Implementation of Walking Therapy in Elderly with Nursing Problems Risk of Falls in Iryou Houjin Fukujukai Nishihara Keiaien Japan - Sari, Diyah Titi; Setianingsih, Setianingsih (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
A person who enters old age will experience a decline in body function which is characterized by reduced hearing function, vision that has begun to deteriorate, decreased muscle strength which causes slowness in carrying out activities so that this can hinder daily activities. The aim of this study was to provide walking therapy to reduce the risk of falls in the elderly in Iryou Houjin Fukujukai Nishihara Keiaien. The method used is a case study which involves several stages of the nursing care process starting from assessment, diagnosis, intervention, implementation and evaluation of nursing, nursing diagnosis of risk of falls related to balance disorders. The results of this case study showed that elderly people with nursing problems were at risk of falling in Iryou Houjin Fukujukai Nishihara Keiaien as much as 75% of the population. From these nursing problems, nursing intervention was carried out by providing walking therapy for approximately 10-15 minutes in 3 days and muscle strength results were obtained. increasing number of elderly people. The increase in muscle strength that occurs in the elderly is not only caused by walking exercise for approximately 10-15 minutes in just 3 days, but there are other additional interventions provided such as providing bone supplements, providing nutrition, and other supportive pharmacological therapies.